Historical memory, embodied in the social space of Minsk, and its influence on the formation of national and European identity of Belarusians - Titarenko, Larissa (Creativity Studies, 2008)
Historical memory embodied in a social space of Minsk represents “cultural signs” of several different epochs. In fact, the historical past of Minsk up to the beginning of the XIX century can be considered as the process of construction of its European identity. In this aspect, the XIX century demonstrated a shift to Russian euro‐asianism, while the soviet history was a unique attempt to construct the universal Soviet identity with only a few features of the national culture. The contemporary epoch gives Minsk a unique chance to simultaneously increase both European and national identity of Belarusians. Istorinė atmintis, įkūnyta socialinėje Minsko erdvėje, ir jos įtaka baltarusių tautinės bei europietiškosios tapatybių formavimuisi Santrauka. Istorinė atmintis, įkūnyta socialinėje Minsko erdvėje, reprezentuoja kelių skirtingų epochų „kultūrinius ženklus“ ir nuo XIX a. pradžios gali būti suprantama kaip europietiškojo tapatumo formavimosi procesas. XIX a. įsigalėjus rusiškajam euroazijatiškumui, visa sovietinė istorija tapo unikaliomis pastangomis sukurti universalų sovietinį tapatumą su keletu blankių nacionalinės kultūros bruožų. Šiuolaikinė epocha teikia galimybę augti tiek europietiškajam, tiek baltarusiškajam tautiniam tapatumui. Reikšminiai žodžiai: istorinė atmintis, tautinis tapatumas, socialinė erdvė, Minskas. First Published Online: 14 Oct 2010